Genetic Diversity and Population Structure of Tomato (Solanum lycopersicum) from the USDA-GRIN Germplasm Collection - Ibtisam Alatawi; Haizheng Xiong; Hanan Alkabkabi; Kenani Chiwina; Qun Luo; Kai-Shu Ling; Yuejun Qu; Renjie Du; Ainong Shi (Agronomy)
The genetic diversity and population structure of tomato (Solanum lycopersicum) were investigated to support breeding strategies and germplasm conservation. A total of 276 accessions from the USDA-GRIN collection were analyzed using single-nucleotide polymorphisms (SNPs) generated through genotyping by sequencing (GBS). After stringent filtering, 5162 high-quality polymorphic SNPs were retained for analysis. Population structure analysis revealed three distinct genetic groups (Q1, Q2, and Q3) among the accessions. Accessions from the USA, Asia, and Central and South America were assigned to all three groups, while accessions from Europe and Oceania were predominantly clustered within Q2. Genetic diversity indices, including major allele frequency, heterozygosity, and polymorphism information content (PIC), indicated moderate-to-high levels of genetic variation. These findings provide essential insights into the genetic diversity and population structure of tomato, offering valuable information for breeding programs aimed at improving traits such as yield, stress tolerance, and disease resistance. The results further underscore the role of global germplasm exchange in shaping the genetic landscape of tomato accessions.